2016
DOI: 10.1155/2016/7684807
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically Assisted Resection of a Rare Mass: Intra-Articular Osteochondroma of Shoulder Originated from Scapula

Abstract: Osteochondromas are the most common benign bone tumors which are mostly seen in the metaphysis of distal femur, proximal tibia, and proximal humerus. As arising from flat bones such as scapula is a rare case, intra-articular osteochondroma is also rare. When the literature is searched it appeared that the scapula and shoulder joint are an uncommon site for osteochondroma. We present a case in which a patient had an osteochondroma placed in shoulder joint and originated from scapula which is a rare situation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
1
5
0
1
Order By: Relevance
“…Similarly to the present report, many studies have demonstrated excellent results in osteochondroma resections of the ventral region of the scapula through scapulothoracic arthroscopy 14, 15…”
Section: Discussionsupporting
confidence: 81%
“…Similarly to the present report, many studies have demonstrated excellent results in osteochondroma resections of the ventral region of the scapula through scapulothoracic arthroscopy 14, 15…”
Section: Discussionsupporting
confidence: 81%
“…Mrad-Dali et al, reported 7 cases out of 95 cases [3]. About 45 cases were also published separately by different authors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Ventral localization like our case was repoted in two cases [19].…”
Section: Discussionmentioning
confidence: 67%
“…Infrequently it can involve flat bones such as the scapula. More often it is painless but in case of size increase it can be painful due to soft tissue compression, skin stretching or pressure effect on nerves and muscles, as well as in the case of fracture through the stalk 6 . An anterior posterior and a Y-view X-Ray check is sufficient to demonstrate the lesion.…”
Section: Discussionmentioning
confidence: 99%